Police law within the system of administrative law: The need of reconciling the relationship - Bezpalova, Olha Ihorivna; Kobzieva , Tatiana Anatoliivna; Valeriiovych Korniienko , Volodymyr; Vasylovych Kritsak, Ivan (DIXI, 2021)
Issues of police control and involvement are of great essence when aspects of administrative law are revealed. The issue here is that there is no way or instances where the legitimate protection of individual rights and freedom can be guaranteed without the presence of the police in ensuring that rights are protected through the respect of the rule of law. The only way this protection can be maintained is only through the operation or application of administrative law. When dealing with the concept of police law, emphasis is laid on the responsibilities this law enforcement agencies have when dealing with matters related to state security, protection of individual living in a given society, and to a certain extent, the entire public. There is no doubt that it is the role of the police to maintain peace and security within a given society, but the question we should be posing is whether their functions performed are done within the confines of respecting fundamental human rights, following the due process of the law being the fundamental and imperative basis or essence of administrative law. One thing is to ensure security, and the other one is to ensure that when enforcing this security, fundamental freedoms and rights of individuals will be respected by the supposed called law enforcement officers. It is therefore in this light that one can say, without any questioning, that under no circumstances should police law function without the intervention of administrative law, both most compliment each other, and activities of the police must be done in strict respect and compliance with that of administrative law.